2021
DOI: 10.3390/insects12090806
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Present in Wheat Kernels Influence the Development of the Grain Weevil (Sitophilus granarius L.)

Abstract: Sitophilus granarius (L.) is considered to be one of the major pests causing damage to cereal grain stored in silos and granaries. Using traditional methods (synthetic insecticides, mechanical, or physical methods) to control this pest is either ineffective or dangerous to people and nature. It is, therefore, necessary to develop new cultivars of cereals that will be distinguished by a high natural tolerance of the foraging by S. granarius. The aim of this study is expressed in the set research hypothesis, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It is assumed that storage pests may be responsible for losses of 30-40% (Abass et al, 2014;Kumar and Kalita, 2017). These are quantitative and qualitative losses related to grain mass loss or excrement and dead insects appearing in the stored product due to insect feeding (Nietupski et al, 2021). The occurrence of insect storage pests contributes to an increase in the temperature and humidity of grain, as a result of which unfavourable biochemical processes occur.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that storage pests may be responsible for losses of 30-40% (Abass et al, 2014;Kumar and Kalita, 2017). These are quantitative and qualitative losses related to grain mass loss or excrement and dead insects appearing in the stored product due to insect feeding (Nietupski et al, 2021). The occurrence of insect storage pests contributes to an increase in the temperature and humidity of grain, as a result of which unfavourable biochemical processes occur.…”
Section: Introductionmentioning
confidence: 99%
“…Maize weevils and other stored grain pests not only devour the whole grain but also cause heat, mildew infection, and caking of stored grain, which significantly decrease grain quantity and compromise the safety of grain storage ( Edde, 2012 ; Antunes et al., 2016 ). After the kernels are infected by stored grain pests, the fat content and gluten content, as well as, sedimentation value decrease.Additionally the acidity increases, that adversely affect the quality of wheat storage and processing ( Keskin and Ozkaya, 2014 ; Nietupski et al., 2021 ). In addition, stored pests excrete feces and larval fragments also affecting quality of the infested grain ( Ortegadorame, 1997 ; Edde, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sitophilus granarius had the highest density in the wheat warehouses of Kütahya province with a rate of 52.6%, followed by O. surinamensis with a rate of 40.2% (Zengin & Karaca, 2020). In addition, it has been reported that these two species are widespread throughout the world (Mason & McDonough, 2012;Correa et al, 2013;Keszthelyi et al, 2021;Nietupski et al, 2021). Grain damaged by these insects decreases in nutritional and market value, as well as in germination percentage and weight.…”
Section: Introductionmentioning
confidence: 99%